Beta-lactamase-mediated imipenem resistance in Bacteroides fragilis. - Cuchural, G J (1986)
Imipenem has excellent antimicrobial activity owing in part to beta-lactamase stability. We found that only 2 of over 350 Bacteroides fragilis group clinical isolates were resistant to imipenem, with an MIC of more than 16 micrograms/ml. These two isolates from the Tufts Anaerobe Laboratory (TAL) were resistant to all other beta-lactam agents tested. The organisms were able to inactivate imipenem in broth cultures and contained similar beta-lactamases that were able to hydrolyze carbapenems, cephamycins, cephalosporins, and penicillins. The molecular sizes of the beta-lactamases in TAL2480 and TAL3636 were estimated to be 44,000 daltons. The novel beta-lactamase contained Zn2+ as a cofactor. An additional factor contributing to resistance was determined. The outer membranes of these two organisms were found to limit free diffusion of the drugs into the periplasm. This novel beta-lactamase, associated with a barrier to drug permeation, resulted in high-grade beta-lactam drug resistance.